Putting people on the map improves the prioritization of ecosystem services. Issue 3 (31st January 2019) - Keeler, Bonnie L; Dalzell, Brent J; Gourevitch, Jesse D; Hawthorne, Peter L; Johnson, Kris A; Noe, Ryan R
Abstract : With limited resources to improve the provision of multiple ecosystem services, conservation programs often rely on spatial tools to identify the best locations for restoration or protection. However, most programs still base prioritization on biophysical metrics that do not fully predict where interventions will deliver the greatest benefits to people. We argue that prioritization metrics need to consider not only biophysical data on the supply of ecosystem services but also socioeconomic data that highlight the value of those services. We use the example of prioritizing best management practices (BMPs) in an agricultural watershed in the US state of Iowa to evaluate how considering the location and preferences of beneficiaries affects the spatial prioritization of investments. We show that adopting metrics that incorporate endpoints of interest and value to people changes the spatial prioritization of BMPs, especially for air quality, lake recreation, and drinking water. Our work demonstrates how publicly available biophysical and social data can be integrated into spatial ecosystem services metrics to enhance the delivered benefits of conservation activities.